Baroreflex control of heart rate in the broad-nosed caiman Caiman latirostris is temperature dependent - Hagensen, Mette K. [UNESP]; Abe, Augusto Shinya [UNESP]; Wang, Tobias (Elsevier B.V., 2010)
It has been suggested that ectothermic vertebrates primarily control blood pressure to protect the pulmonary vasculature from oedema caused by high pressure, while endothermic vertebrates control blood pressure to maintain adequate oxygen delivery to the tissues. In the present study we have characterised how temperature affects the cardiac limb of the baroreflex in the intact unanaesthetized broad-nosed caiman (Caiman latirostris) by pharmacological manipulation of blood pressure in a closed-loop system. Sodium nitroprusside (SNIP) and phenylephrine were used to manipulate arterial pressure and the resulting alterations in heart rate were used to calculate the gain of the baroreflex. Both drugs were infused as bolus injections in concentrations of 5, 10, 25, 50 and 100 mu g kg(-1). The barostatic response was present at both 15 and 30 degrees C, and, at both temperatures, C. latirostris responded to reductions in systemic blood pressure (Psys). At 30 degrees C the baroreflex was more pronounced at a blood pressure lower than control value (52.3 cmH(2)O) with a maximal baroreflex gain of 1.97 beats min(-1) cmH(2)O(-1) at a Psys of 41.9 cmH(2)O, and therefore seems to counteract hypotension. In contrast, the maximal baroreflex at 15 degrees C was found at a Psys almost equal to the control value. The highest baroreflex gain in response to change in blood pressure was measured at the highest temperature. Thus, C. latirostris exhibit a temperature dependent barostatic response. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Reptile; Cardiovascular; Blood pressure regulation